The emergence and contested growth of social enterprise in Thailand. Issue 2 (4th May 2021) - Doherty, Bob; Kittipanya-Ngam, Pichawadee
ABSTRACT: This paper investigates the development of the Social Enterprise (SE) in Thailand. Emerging from the non-profit sector in the 1970s, Thailand is now experiencing the development of new state-private policy interventions to stimulate development of SE. We combine the work of Kerlin on the socio-economic environment with the theories of market creation from economic sociology. We pinpoint for the first time the key institutions, networks, cognitive framings and policy initiatives of SE emergence and development in Thailand. In addition, we identify a new country type Social Enterprise Semi Strategic Diverse model form, we term an Authoritarian State-Corporate model.